2019
DOI: 10.1111/1365-2435.13402
|View full text |Cite
|
Sign up to set email alerts
|

Geographic scale and disturbance influence intraspecific trait variability in leaves and roots of North American understorey plants

Abstract: Considering intraspecific trait variability (ITV) in ecological studies has improved our understanding of species persistence and coexistence. These advances are based on the growing number of leaf ITV studies over local gradients, but logistical constraints have prevented a solid examination of ITV in root traits or at scales reflecting species’ geographic ranges. We compared the magnitude of ITV in above‐ and below‐ground plant organs across three spatial scales (biophysical region, locality and plot). We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 74 publications
4
46
2
Order By: Relevance
“…S4). Prior studies also observed idiosyncratic patterns in leaf (Albert et al, 2010;Kichenin et al, 2013;Read et al, 2017) and root trait variation along various environmental gradients (Kumordzi et al, 2019;Roybal & Butterfield, 2019;Zhou et al, 2019) suggesting that idiosyncrasy in intraspecific trait patterns may be a widespread phenomenon. As the different degrees of,…”
Section: Idiosyncratic Root Trait Patterns Along a Complex Environmenmentioning
confidence: 92%
See 4 more Smart Citations
“…S4). Prior studies also observed idiosyncratic patterns in leaf (Albert et al, 2010;Kichenin et al, 2013;Read et al, 2017) and root trait variation along various environmental gradients (Kumordzi et al, 2019;Roybal & Butterfield, 2019;Zhou et al, 2019) suggesting that idiosyncrasy in intraspecific trait patterns may be a widespread phenomenon. As the different degrees of,…”
Section: Idiosyncratic Root Trait Patterns Along a Complex Environmenmentioning
confidence: 92%
“…Defrenne et al (2019) also found that their smallest sampling scalesi.e., the individual root branch and the soil blocks from which roots were collectedexplained up to 100 % of root trait variation of Douglas fir trees along a 600-km, biogeographic gradient in Canada. Similarly, Kumordzi et al (2019) showed that a large part of root trait variation was explained at the local (i.e., sites within their gradient with comparable climate and soil characteristics) rather than at the regional scale (i.e., their ~5000 km long gradient). The large heterogeneity of soils at small spatial scales (Ettema & Wardle, 2002) may cause roots to respond to very local soil properties, for example by producing more lateral roots when encountering a nutrient-rich patch (Hodge, 2004).…”
Section: Low Intraspecific Variation In Root Traits With Elevationmentioning
confidence: 96%
See 3 more Smart Citations